2014
DOI: 10.1111/jvim.12318
|View full text |Cite
|
Sign up to set email alerts
|

Age Effects on Blood Gas, Spirometry, Airway Reactivity, and Bronchoalveolar Lavage Fluid Cytology in Clinically Healthy Horses

Abstract: BackgroundDespite the increasing number of geriatric horses attended by veterinarians, there is a lack of understanding of aging‐related changes on the respiratory system of horses.ObjectiveTo identify aging‐related changes on the respiratory function and bronchoalveolar lavage fluid (BALF) cytology of horses.AnimalsFifteen healthy young adult (2–11 years) and 16 healthy aged (≥20 years) horses.MethodsThe respiratory system was examined by measurement of arterial blood gases (ABG), use of respiratory inductive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
15
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 34 publications
6
15
1
Order By: Relevance
“…In the current study, horses averaged a tidal volume of 7.89 ± 1.43 L (mean ± stdev) and respiratory frequency of 12 bpm during eupnoeic respiration, which is similar to previous studies using ultrasound or Fleisch-type pneumotachometers [3235], and slightly greater than values determined by respiratory inductance plethysmography and pneumotachography [25, 36]. In addition to differences due to technique, it is possible that equipment differences, such as mask volume and airflow resistance, or physiological differences between horses, such as age [36], use [35] or sub-clinical airway disease [34, 35], may influence values determined during pulmonary function testing.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In the current study, horses averaged a tidal volume of 7.89 ± 1.43 L (mean ± stdev) and respiratory frequency of 12 bpm during eupnoeic respiration, which is similar to previous studies using ultrasound or Fleisch-type pneumotachometers [3235], and slightly greater than values determined by respiratory inductance plethysmography and pneumotachography [25, 36]. In addition to differences due to technique, it is possible that equipment differences, such as mask volume and airflow resistance, or physiological differences between horses, such as age [36], use [35] or sub-clinical airway disease [34, 35], may influence values determined during pulmonary function testing.…”
Section: Discussionsupporting
confidence: 88%
“…In addition to differences due to technique, it is possible that equipment differences, such as mask volume and airflow resistance, or physiological differences between horses, such as age [36], use [35] or sub-clinical airway disease [34, 35], may influence values determined during pulmonary function testing. Hyperpnoea induced by carbon dioxide rebreathing was investigated in the current study because previous studies have suggested that PFT during tidal breathing is insensitive for detection of subtle changes, such as those associated with IAD [14, 16, 17].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, regardless of the definition used to identify horses with a cytological diagnosis of IAD, the absence of AHR (50%) was more common than previously reported . Some caution, however, must be used in assessing the functional significance of abnormal BAL findings.…”
Section: Discussionmentioning
confidence: 63%
“…This phenomenon, whereby cytological evidence of airway inflammation does not correlate with bronchial hyper‐reactivity, has been reported in both horses and humans . Increased numbers of inflammatory cells in the airways of human athletes are not necessarily associated with any major clinical or functional alterations .…”
Section: Discussionmentioning
confidence: 91%
“…When BALF cytology using definition one (lower cut off percentages) was used a greater number of horses were considered abnormal, but their airway reactivity, as determined by PC 35, was similar to cytologically normal horses. This finding is similar to another study using the same definition and methodology for assessing airway hyperactivity in athletic horses, and is also consistent with studies of sedentary horses where BALF cytology was performed without a history of poor performance or overt respiratory tract signs . A contrasting study by Bedenice et al using the same methodology to measure AHR and airway cytology concluded that a relative mast cell percentage of > 2% was associated with AHR.…”
Section: Discussionmentioning
confidence: 99%